Intestinal microbiota is altered in patients with colon cancer and modified by probiotic intervention - Ashley A Hibberd; Anna Lyra; Arthur C Ouwehand; Peter Rolny; Helena Lindegren; Lennart Cedgård; Yvonne Wettergren (BMJ Open Gastroenterology)
Objective The colonic microbiota is altered in patients with colorectal cancer (CRC). We investigated the microbiota composition of patients with colon cancer compared with controls devoid of neoplastic or inflammatory disease and the potential to modify the colonic microbiota with probiotics.Design Biopsy samples were obtained from the normal mucosa and tumour during colonoscopy from 15 patients with colon cancer. Subsequent patient-matched samples were taken at surgery from the tumour and nearby mucosa from the patients with cancer, eight of whom had received two daily tablets totalling 1.4×1010 CFUs Bifidobacterium lactis Bl-04 and 7×109 CFUs Lactobacillus acidophilus NCFM. Faecal samples were obtained after colonoscopy prior to starting the intervention and at surgery. In addition, 21 mucosal biopsies from non-cancer controls were obtained during colonoscopy followed by later faecal samples. The colonic and faecal microbiota was assessed by 16S rRNA gene amplicon sequencing.Results The tumour microbiota was characterised by increased microbial diversity and enrichment of several taxa including Fusobacterium, Selenomonas and Peptostreptococcus compared with the control microbiota. Patients with colon cancer that received probiotics had an increased abundance of butyrate-producing bacteria, especially Faecalibacterium and Clostridiales spp in the tumour, non-tumour mucosa and faecal microbiota. CRC-associated genera such as Fusobacterium and Peptostreptococcus tended to be reduced in the faecal microbiota of patients that received probiotics.Conclusions Patients with colon cancer harbour a distinct microbiota signature in the tumour tissue and nearby mucosa, which was altered with probiotic intervention. Our results show promise for potential therapeutic benefits in CRC by manipulation of the microbiota.Trial registration number NCT03072641; Results.